„Twardego snu pieczęcie”. Świat dziwów w „Zaklętym mieście” Edwarda Leszczyńskiego - Igliński, Grzegorz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article offers an analysis and interpretation of the poem Zaklęte miasto [Enchanted city] from the volume Ballady i pieśni [Ballads and songs] by the Young Poland poet Edward Leszczyński. The poem is first analysed based on the oneiric convention. For this purpose the author refers to the philosophy of Arthur Schopenhauer and explains the symbolism of the wheel, which indicates the sense of entrapment in the world, a situation with no way out. The dreaming-wandering from Leszczyński’s poem, the gaining and losing of faith, is then examined in the context of August Strindberg’s A Dream Play. The two works, ostensibly so different, address with a similar kind of poetic “dreaming.” In both cases, the life in question is inauthentic, asleep, affected by a curse, kept under a spell. The last stanza of the poem indicates the Dionysian tradition, and therefore makes it necessary to refer to the philosophy of Friedrich Nietzsche and his idea of eternal return. The examination lead to the conclusion that Leszczyński’s work refers to the dual meaning of circularity, or rather two attitudes towards life. In the first case Schopenhauerian determinism is revealed, according to which life is a monotonous, enchaining, ominous dream. In the second case we are dealing with the worship life of Nietzschean provenance – one may, therefore, conclude that a curse can be a blessing and being asleep can be being awake, if we accept the eternal return.